2017
DOI: 10.1016/j.joa.2017.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Influence of proton pump inhibitors on blood dabigatran concentrations in Japanese patients with non‐valvular atrial fibrillation

Abstract: BackgroundDabigatran is a direct thrombin inhibitor used to decrease the risk of ischemic stroke in patients with non-valvular atrial fibrillation (NVAF). Its prodrug, dabigatran etexilate (DE) is often co-administrated with a proton pump inhibitor (PPI) because of its adverse effects on the gastrointestinal tract. Drug-drug interactions between DE and PPIs in daily clinical practice have not been fully elucidated.MethodsChanges in blood dabigatran concentration (DC) were investigated using the dilute thrombin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 17 publications
(33 reference statements)
0
18
0
Order By: Relevance
“…In this study, there were no significant differences between the PPIs in dabigatran trough (62. 20 showed in patients with AF on DT no significant differences in trough and peak dabigatran plasma levels among three different PPIs (lansoprazole, rabeprazole, and esomeprazole). Thus, currently available data suggest that the PPI-dabigatran interaction is rather a "class" than "drug" effect, and that there are no significant differences in this interaction among different PPIs.…”
Section: Does Ppi Impact Dabigatran Plasma Levels?mentioning
confidence: 87%
See 3 more Smart Citations
“…In this study, there were no significant differences between the PPIs in dabigatran trough (62. 20 showed in patients with AF on DT no significant differences in trough and peak dabigatran plasma levels among three different PPIs (lansoprazole, rabeprazole, and esomeprazole). Thus, currently available data suggest that the PPI-dabigatran interaction is rather a "class" than "drug" effect, and that there are no significant differences in this interaction among different PPIs.…”
Section: Does Ppi Impact Dabigatran Plasma Levels?mentioning
confidence: 87%
“…Comparing those with and without PPI, dabigatran trough and peak levels were significantly lower in individuals receiving PPI. Moreover, in an open-label, randomized, two-period crossover study in Japanese AF patients, 20 the authors demonstrated (►Table 3) significantly lower dabigatran trough and peak levels in those with PPI compared with those without PPI. Therefore, PPI administrated together with DT in patients with AF significantly reduced dabigatran on treatment plasma levels in two postmarketing clinical studies 19,20 ; most probably through the effect on gastric pH.…”
Section: Does Ppi Impact Dabigatran Plasma Levels?mentioning
confidence: 95%
See 2 more Smart Citations
“… 131 , 134 , 135 However, the interaction of PPIs and the direct thrombin inhibitor dabigatran was reported (low on-treatment level of dabigatran) from recently published studies. 136 - 138 Potential adverse events related to the long-term use of PPIs is another concern. Therefore, balancing the risk-benefit approach is still necessary before the co-prescription of anticoagulants and acid suppressants.…”
Section: Consensus Statementsmentioning
confidence: 99%